DOSE ANALYZE OF BORON NEUTRON CAPTURE THERAPY (BNCT) AT SKIN CANCER MELANOMA USING MCNPX WITH NEUTRON SOURCE FROM THERMAL COLUMN OF KARTINI REACTOR - Siti Rosidah; Yohannes Sardjono; Yosaphat Sumardi (Indonesian Journal of Physics and Nuclear Applications, 2017)
This research aims to determine the amount of radiation dose rate that can be accepted and the irradiation time that is required from Boron Neutron Capture Therapy (BNCT) cancer therapy to treat melanoma skin cancer. This research used the simulation program, MCNPX by defining the geometric dimensions of the tissue component, and describing the radiation source that were used. The outputs obtained from the MCNPX simulation were the neutron flux and the neutron scattering dose that came out from the collimator. The value of neutron flux was used to calculate the dose which comes from the interaction between the neutron and the material in the cancer tissue. Based on the results of the research, the dose rate to treat cancer tissue for boron is 10 μg/g of tumor, which translates to about 0.019241 Gy/second and  requires 25.98 minutes of irradiation time, 15 μg/g of tumor translates to 0.021854 Gy/second and requires 2.,87 minutes, 20 μg/g of tumor translates to 0.022902 Gy/second and requires 21,83 minutes, 25 μg/g of tumor translates to 0.0271275 Gy/second and requires 18.43 minutes, 30 μg/g of tumor translates to 0.0297658 Gy/second and requires 16.79 minutes, and 35 μg/g of tumor translates to 0.0343472 Gy/second and requires 14.55 minutes . The irradiation time needed for cancer tissue is shorter when boron concentration greater at the cancerous tissue.